TINJAUAN KONDISI RENTAN PADA PERMASALAHAN PSIKOLOGIS KDRT & PEMERKOSAAN DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP3A) KABUPATEN BEKASI - Sirait, Lenny Irmawaty; Dea, Dea; Enika, Enika; Ernawati, Ernawati; Oktaviani, Evi; Mubarokah, Novia; Nursalima, Rafidah Rahmah; Indriyani, Siti (STIKes Medistra Indonesia, 2026)
When people talk about violence against women, it can be said that women in any situation remain vulnerable to becoming victims of oppressive structures or systems (social, cultural, or political). This is reinforced by the opinion that the weak position of women makes them less empowered to protect themselves. It is said that even women who are at home can become victims of violence from their husbands, women in the workplace can also receive sexual harassment and even rape from their superiors or co-workers. This study aims to review the vulnerable condition of psychological problems in domestic violence and rape. This type of research is qualitative with a phenomenological approach. Interviews were conducted directlywith key informants and supporting informants using in-depth interview guidelines. The results of the study found that 1) The causes of domestic violence on victims are economic factors 2) The psychological impact experienced by victims of domestic violence is a feeling of hopelessness and experienced trauma 3) The causes of harassment because the perpetrator was drunk with alcohol and supported by a quiet scene 4) The psychological impact experienced by victims of rape is that the victim becomes traumatized when she sees the perpetrator of the abuse.